Antibacterial nanofiltration membrane and preparation method thereof

By constructing a stable antibacterial structure inside the separation layer of the nanofiltration membrane, the problems of biofilm growth and antibacterial agent loss in the treatment of hospital wastewater by polyamide nanofiltration membranes are solved, achieving a comprehensive improvement in long-lasting antibacterial effect, anti-fouling properties, and highly selective separation.

CN121668983AActive Publication Date: 2026-03-17SHANDONG ZHAOJIN MOTIAN
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202610178437.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-09
Publication Date
2026-03-17
Estimated Expiration
2046-02-09

AI Technical Summary

Technical Problem

When treating hospital wastewater, existing polyamide nanofiltration membranes are prone to biofilm growth on their surface, leading to performance degradation. Furthermore, the surface-modified antibacterial agents are rapidly lost due to poor interfacial stability, making it difficult to achieve both long-lasting antibacterial effect and separation stability.

Method used

A stable structure is constructed inside the nanofiltration membrane separation layer through interfacial polymerization and subsequent anchoring reaction. Guanidin-containing cations and zwitterions are introduced, and maleimide crosslinking anchoring agents are used to form strongly cationic antibacterial sites and a surface amphoteric hydration layer. Combined with alternating acid/alkali treatment and thermal curing, a synergistically distributed antibacterial structure is formed.

Benefits of technology

It achieves long-term stability of antibacterial properties and antifouling ability, maintains high selective separation performance, extends membrane life and reduces operation and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121668983A_ABST
    Figure CN121668983A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membranes, in particular to an antibacterial nanofiltration membrane and a preparation method thereof. The method comprises the following steps: carrying out polyethyleneimine / tannic acid pretreatment on a polyethersulfone ultrafiltration membrane base material; sequentially carrying out first interfacial polymerization on a water phase containing piperazine, agmatine sulfate and taurine and an organic phase containing trimesoyl chloride; carrying out secondary water-phase re-leaching by adopting a taurine solution; preparing a crosslinking anchoring agent which retains 20%-22% of maleimide double bonds; the composite material and trimesoyl chloride are jointly used for anchoring-densification treatment; and finally, carrying out acid / alkali alternation and thermocuring. Through unique step design and functional component cooperation, a stable antibacterial and anti-pollution structure is constructed in the separation layer, and the problems that a traditional nanofiltration membrane is prone to biological pollution and an antibacterial agent is prone to loss are solved. The obtained membrane has the advantages of long-acting antibiosis, high flux recovery rate, high ion selectivity and excellent acid and alkali resistant cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane technology, and in particular to an antibacterial nanofiltration membrane and its preparation method. Background Technology

[0002] Hospital wastewater is complex, containing not only conventional pollutants but also high concentrations of pathogenic microorganisms, residual antibiotics, and disinfectants, posing a significant challenge to advanced treatment and reuse technologies. Nanofiltration technology is considered a key process in this field due to its highly efficient retention of trace organic matter and multivalent ions. Among these, polyamide composite nanofiltration membranes are widely used due to their excellent separation performance; however, in actual operation, especially when treating hospital wastewater with high microbial loads over long periods, the membrane surface can easily become a breeding ground for bacteria.

[0003] The initial adhesion of bacteria to the membrane surface is the first step in biofilm formation. Since the surface of traditional polyamide separation layers is typically negatively charged and somewhat hydrophobic, it provides non-specific adsorption sites for negatively charged bacteria, further accelerating microbial colonization. Once a dense biofilm forms, it not only significantly increases membrane filtration resistance, leading to irreversible decline in water flux, but also exacerbates membrane material degradation due to biological metabolic activity, shortening membrane lifespan.

[0004] To suppress biofouling, researchers often modify nanofiltration membranes by surface grafting or coating with antibacterial agents. For example, broad-spectrum antibacterial agents such as silver ions and quaternary ammonium salts are introduced. However, these physically coated or simply blended antibacterial agents exhibit problems of easy leaching and deactivation during long-term operation, especially under the complex chemical environment of hospital wastewater (such as residual chlorine and oxidizing disinfectants) and dynamic hydraulic flushing. The rapid loss of antibacterial agents not only makes it difficult to maintain antibacterial performance, but more seriously, the pores or defects left after loss may damage the integrity of the polyamide separation layer, causing a decrease in selectivity and even becoming new pollution accumulation points.

[0005] On the other hand, to improve the fixation rate of antimicrobial agents, some studies have attempted to immobilize antimicrobial molecules through strong covalent bonding. However, excessive cross-linking or the introduction of excessively rigid antimicrobial segments often leads to the polyamide layer becoming brittle and hard. Under long-term pressure and pH fluctuations, interfacial stress concentration can easily induce microcracks, which also impair the long-term separation stability and mechanical durability of the membrane. Therefore, how to construct an antimicrobial structure within the nanofiltration membrane that has long-lasting antimicrobial activity, is firmly bonded to the substrate, and does not affect the inherent transport channels of the separation layer is the key to overcoming the current technological bottleneck. Existing technologies have not yet effectively solved the balance problem between antimicrobial function and separation stability, which restricts the further application of nanofiltration technology in high-standard hospital wastewater reuse. Summary of the Invention

[0006] In view of this, the purpose of this invention is to propose an antibacterial nanofiltration membrane and its preparation method, so as to solve the problems that existing polyamide nanofiltration membranes are prone to biofilm growth on their surface when treating hospital wastewater, which leads to performance degradation, and the surface-modified antibacterial agents are quickly lost due to poor interfacial stability, making it difficult to achieve both long-term antibacterial effect and separation stability.

[0007] To achieve the above objectives, the present invention provides a method for preparing an antibacterial nanofiltration membrane, comprising the following steps: (1) Interface layer pretreatment: Immerse the polyethersulfone ultrafiltration membrane substrate in a pretreatment solution prepared by deionized water, branched polyethyleneimine and tannic acid for 10-30 min, take it out and rinse it to obtain the pretreated substrate; (2) First interface polymerization: The pretreated substrate is immersed in an aqueous phase containing piperazine, guanidinobutylamine sulfate, taurine, sodium bicarbonate and polysorbate 20 for 5-15 min, and the excess liquid is removed by rolling. Then it is immersed in an isoalkane organic phase containing trimesoyl chloride for 5-15 min, and the excess liquid is removed by rolling to obtain surface treated substrate B. (3) Secondary aqueous phase immersion: Immerse the surface-treated substrate B in a water / isopropanol mixed solution containing taurine for 3-7 minutes, roll to remove excess liquid, and obtain surface-treated substrate C; (4) Preparation of maleimide crosslinking anchoring agent: After reacting 4,4′-bismaleimide diphenylmethane with taurine and triethylamine in N,N-dimethylformamide, aminoguanidine bicarbonate is added to continue the reaction to obtain a crosslinking anchoring agent that retains part of the maleimide double bond; (5) Anchoring-densification: The crosslinking anchoring agent is added to the isoalkane organic phase containing trimesoyl chloride, the surface-treated substrate C is immersed for 15-25 min and rolled to remove excess liquid, to obtain the surface-treated substrate D; (6) Acid / alkali alternation and heat curing: The surface-treated substrate D is immersed in citric acid monohydrate solution and sodium bicarbonate solution in sequence, rinsed, and cured under hot air at 80-90°C for 5 minutes to obtain an antibacterial nanofiltration membrane.

[0008] Preferably, in step (1), the polyethyleneimine is branched and has a weight-average molecular weight of 24,000-26,000.

[0009] Preferably, in step (1), the polyethersulfone ultrafiltration membrane substrate has a size of 200mm×200mm, a molecular weight cutoff of 28-32kDa, and a thickness of 115-125μm.

[0010] Preferably, in step (1), the pretreatment solution is prepared by dissolving 1-3g of branched polyethyleneimine and 0.5-1.5g of tannic acid in 1000mL of deionized water.

[0011] Preferably, in step (2), the aqueous phase is prepared by adding 3-5g piperazine, 0.5-1.5g guanidinobutylamine sulfate, 3-7g taurine, 0.5-1.5g sodium bicarbonate and 0.5-1.5g polysorbate 20 to every 1000mL of deionized water.

[0012] Preferably, the organic phase in step (2) is 0.5-1.5 g of pyromellitic chloride dissolved in 1000 mL of Isopar G.

[0013] Preferably, the mixed solution in step (3) is a mixture of 950 mL of deionized water and 50 mL of isopropanol, and 7-13 g of taurine is dissolved in it.

[0014] Preferably, in step (4), the mass ratio of 4,4′-bismaleimide diphenylmethane, taurine, triethylamine and aminoguanidine bicarbonate is 5:3:2:1.

[0015] Preferably, the amount of double bond retention in the crosslinking anchoring agent that retains part of the maleimide double bond in step (4) is 20%-22%.

[0016] Preferably, in step (5), 0.03-0.07g of crosslinking anchoring agent is pre-dissolved in 10mL of ethyl acetate and added to 1000mL of IsoparG, and 0.8-1.2g of trimesoyl chloride is added.

[0017] Preferably, in step (6), the acidic stage involves dissolving 1-3g of citric acid monohydrate in 2000mL of deionized water and immersing it for 1-3 minutes, while the alkaline stage involves dissolving 1-3g of sodium bicarbonate in 2000mL of deionized water and immersing it for 1-3 minutes.

[0018] The present invention also provides an antibacterial nanofiltration membrane, which is obtained by the above-described method for preparing the antibacterial nanofiltration membrane.

[0019] The beneficial effects of this invention are: This invention constructs a stable structure with synergistic functions within the nanofiltration membrane separation layer through a unique interfacial polymerization and subsequent anchoring reaction design, thereby comprehensively improving the membrane's performance.

[0020] The nanofiltration membrane obtained by this invention exhibits significantly enhanced antimicrobial durability. The antimicrobial components stably present in the membrane separation layer can effectively act on contacting microorganisms for a long time. Even under long-term hydraulic scouring, its antimicrobial performance can still maintain a high level, effectively inhibiting the formation of biofilm and providing a guarantee for the long-term stable operation of the membrane in microbial enrichment environments.

[0021] This membrane exhibits excellent antifouling properties and easy cleaning characteristics. The membrane surface properties have been optimized, significantly reducing the initial adhesion of proteinaceous contaminants and bacteria. After fouling occurs, high-flux recovery can be achieved through simple physical cleaning, reducing the frequency and intensity of chemical cleaning, thus extending membrane lifespan and lowering operating and maintenance costs.

[0022] This invention achieves highly efficient antibacterial and antifouling effects while maintaining the nanofiltration membrane's high selective separation capability for salts. It maintains an extremely high rejection rate for divalent ions such as sulfate, while exhibiting some permeability to monovalent ions, demonstrating excellent selective separation characteristics and meeting the technical requirements for deep desalination and resource recovery.

[0023] This nanofiltration membrane exhibits excellent long-term operational stability and durability. Despite acid / alkali cleaning cycles or fluctuations in influent pH, the membrane maintains good structural integrity, separation performance, and functionality. This indicates that the membrane's internal functional structure is firmly integrated with the separation matrix, capable of withstanding certain chemical and physical shocks, and adapting to complex real-world water quality environments.

[0024] In summary, this invention successfully integrates long-lasting antibacterial properties, high-efficiency antifouling, highly selective separation, and excellent durability. The various functions work synergistically, rather than being simply additive, achieving a comprehensive improvement in membrane performance and providing an effective solution to the challenges of membrane fouling and biosafety in the advanced treatment of hazardous wastewater. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0026] Figure 1 The image shows the infrared spectrum of the antibacterial nanofiltration membrane surface coating powder sample in Example 2 of this invention. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. Example 1

[0028] (1) Dissolve 1g of polyethyleneimine (branched type, weight average molecular weight of about 25,000, Sigma-Aldrich, catalog number P434400) and 0.5g of tannic acid in 1000mL of deionized water to obtain a pretreatment solution; completely immerse a polyethersulfone ultrafiltration membrane (size 200mm×200mm, molecular weight cutoff of about 30kDa, thickness of 120μm) for 10min, remove it and rinse it with deionized water to obtain a pretreated substrate; (2) Preparation of aqueous phase: Add 3g piperazine, 0.5g guanidinobutylamine sulfate, 3g taurine, 0.5g sodium bicarbonate and 0.5g polysorbate 20 to 1000mL deionized water, stir for 5min, completely immerse the pretreated substrate for 5min, roll to remove the excess liquid to obtain surface treated substrate A. Preparation of organic phase: Dissolve 0.5g trimesoyl chloride in 1000mL of isoparaffinic alkane Mobil Isopar G solvent, then completely immerse surface treated substrate A for 5min, roll to remove the excess liquid to obtain surface treated substrate B. (3) Dissolve 7g of taurine in a mixed solvent of 950mL deionized water and 50mL isopropanol, then completely immerse the surface-treated substrate B for 3min, roll it to remove the excess liquid, and obtain the surface-treated substrate C. (4) Dissolve 5g of 4,4'-bismaleimide diphenylmethane in 500mL of N,N-dimethylformamide, add 3g of taurine and 2g of triethylamine, stir at 50°C for 120min; after cooling to room temperature, add 1g of aminoguanidine bicarbonate, stir for another 120min, and rotary evaporate to obtain maleimide crosslinking anchoring agent (quantitatively determined by 302nm UV to retain 21.1% of maleimide double bonds). (5) First, pre-dissolve 0.03g of maleimide crosslinking anchoring agent in 10mL of ethyl acetate, then add it to 1000mL of isoparaffinic Mobil Isopar G solvent and add 0.8g of trimesoyl chloride. Stir for 10min, immerse the surface-treated substrate C for 15min, roll to remove excess liquid, and obtain the surface-treated substrate D. (6) Dissolve 1g of citric acid monohydrate in 2000mL of deionized water and immerse the surface-treated substrate D completely for 1min. Then dissolve 1g of sodium bicarbonate in 2000mL of deionized water and immerse it for another 1min. Finally, rinse with deionized water and cure under 80°C hot air for 5min to obtain an antibacterial nanofiltration membrane. Example 2

[0029] (1) Dissolve 2g of polyethyleneimine (branched type, weight average molecular weight of about 25,000, Sigma-Aldrich, catalog number P434400) and 1g of tannic acid in 1000mL of deionized water to obtain a pretreatment solution; completely immerse a polyethersulfone ultrafiltration membrane (size 200mm×200mm, molecular weight cutoff of about 30kDa, thickness of 120μm) for 20min, remove it and rinse it with deionized water to obtain a pretreated substrate; (2) Preparation of aqueous phase: Add 4g piperazine, 1g guanidinobutylamine sulfate, 5g taurine, 1g sodium bicarbonate and 1g polysorbate 20 to 1000mL deionized water, stir for 10min, completely immerse the pretreated substrate for 10min, roll to remove the excess liquid to obtain surface treated substrate A. Preparation of organic phase: Dissolve 1g trimesoyl chloride in 1000mL of isoparaffinic alkane Mobil Isopar G solvent, then completely immerse surface treated substrate A for 10min, roll to remove the excess liquid to obtain surface treated substrate B. (3) Dissolve 10g of taurine in a mixed solvent of 950mL deionized water and 50mL isopropanol, then completely immerse the surface-treated substrate B for 5min, roll it to remove the excess liquid, and obtain the surface-treated substrate C. (4) Dissolve 5g of 4,4'-bismaleimide diphenylmethane in 500mL of N,N-dimethylformamide, add 3g of taurine and 2g of triethylamine, stir at 50°C for 120min; after cooling to room temperature, add 1g of aminoguanidine bicarbonate, stir for another 120min, and rotary evaporate to obtain maleimide crosslinking anchoring agent (quantitative determination by 302nm UV showed that 21.2% of maleimide double bonds were retained). (5) First, pre-dissolve 0.05g of maleimide crosslinking anchoring agent in 10mL of ethyl acetate, then add it to 1000mL of isoparaffinic Mobil Isopar G solvent and add 1g of trimesoyl chloride. Stir for 10min, immerse the surface-treated substrate C for 20min, roll to remove excess liquid, and obtain the surface-treated substrate D.

[0030] (6) Dissolve 2g of citric acid monohydrate in 2000mL of deionized water and immerse the surface-treated substrate D completely for 2min. Then dissolve 2g of sodium bicarbonate in 2000mL of deionized water and immerse it for another 2min. Finally, rinse with deionized water and cure under 85°C hot air for 5min to obtain an antibacterial nanofiltration membrane. Example 3

[0031] (1) Dissolve 3g of polyethyleneimine (branched type, weight average molecular weight of about 25,000, Sigma-Aldrich, catalog number P434400) and 1.5g of tannic acid in 1000mL of deionized water to obtain a pretreatment solution; completely immerse a polyethersulfone ultrafiltration membrane (size 200mm×200mm, molecular weight cutoff of about 30kDa, thickness of 120μm) for 30min, remove it and rinse it with deionized water to obtain a pretreated substrate; (2) Preparation of aqueous phase: Add 5g piperazine, 1.5g guanidinobutylamine sulfate, 7g taurine, 1.5g sodium bicarbonate and 1.5g polysorbate 20 to 1000mL deionized water, stir for 15min, completely immerse the pretreated substrate for 15min, roll to remove the excess liquid to obtain surface treated substrate A. Preparation of organic phase: Dissolve 1.5g trimesoyl chloride in 1000mL of isoparaffinic alkane Mobil Isopar G solvent, then completely immerse surface treated substrate A for 15min, roll to remove the excess liquid to obtain surface treated substrate B. (3) Dissolve 13g of taurine in a mixed solvent of 950mL deionized water and 50mL isopropanol, then completely immerse the surface-treated substrate B for 7min, roll it to remove the excess liquid, and obtain the surface-treated substrate C. (4) Dissolve 5g of 4,4'-bismaleimide diphenylmethane in 500mL of N,N-dimethylformamide, add 3g of taurine and 2g of triethylamine, stir at 50°C for 120min; after cooling to room temperature, add 1g of aminoguanidine bicarbonate, stir for another 120min, and rotary evaporate to obtain maleimide crosslinking anchoring agent (quantitatively determined by 302nm UV to retain 20.9% of maleimide double bonds). (5) First, pre-dissolve 0.07g of maleimide crosslinking anchoring agent in 10mL of ethyl acetate, then add it to 1000mL of isoparaffinic Mobil Isopar G solvent and add 1.2g of trimesoyl chloride. Stir for 10min, immerse the surface-treated substrate C for 25min, roll to remove excess liquid, and obtain the surface-treated substrate D. (6) Dissolve 3g of citric acid monohydrate in 2000mL of deionized water and immerse the surface-treated substrate D completely for 3min. Then dissolve 3g of sodium bicarbonate in 2000mL of deionized water and immerse it for another 3min. Finally, rinse with deionized water and cure under 90°C hot air for 5min to obtain an antibacterial nanofiltration membrane.

[0032] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that taurine is not added to the aqueous phase in step (2), while the other conditions are the same as in Example 2.

[0033] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that guanidinobutylamine sulfate is not added to the aqueous phase in step (2), and the other conditions are the same as in Example 2.

[0034] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (3) is omitted, while the other conditions are the same as in Example 2.

[0035] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that maleimide crosslinking anchoring agent is not added to the organic phase in step (5), while the other conditions are the same as in Example 2.

[0036] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that: in step (4) when preparing the maleimide crosslinking anchoring agent, the amount of aminoguanidine bicarbonate was adjusted to 2g (the other ratios, temperature and stirring time were the same), so that the amount of maleimide double bond retention measured by 302nm UV was 0, and the other conditions were the same as in Example 2.

[0037] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the pretreatment of the polyethyleneimine / tannic acid weak interface layer in step (1) is omitted (the substrate is only rinsed with deionized water before proceeding to step (2)); the other conditions are the same as in Example 2.

[0038] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (6) only involves immersion in the "citric acid monohydrate acid segment" and omits the "sodium bicarbonate alkaline segment", while the other conditions are the same as in Example 2.

[0039] Performance testing: Infrared spectroscopy: The coating on the substrate surface of Example 2 was scraped off with a scraper, dried, and then subjected to infrared spectroscopy scanning at a resolution of 4 cm⁻¹. -1 Range 4000-650cm -1 .

[0040] Surface Zeta potential: according to GB / T37617-2019, at 1 mmol·L⁻¹ -1 Potassium chloride solution, 25°C, pH 7.0, three measurements were taken on the same membrane and the average was taken. The results are shown in Table 1.

[0041] Water contact angle: According to GB / T30693-2014, the static drip method was used, with a drop volume of 3µL, and the average of 5 points was collected. The results are shown in Table 1.

[0042] Antibacterial properties and antibacterial rinse resistance: According to GB / T37206-2018, *Escherichia coli* ATCC8739 and *Staphylococcus aureus* ATCC6538 were selected, with an inoculum size of (2.5±0.5)×10⁻⁶. 5 CFU·cm -2 The antibacterial rate was maintained after rinsing with deionized water at 0.5 MPa for 24 hours at 35°C for 50 hours, followed by cross-flow rinsing with deionized water for 50 hours. The results are shown in Table 1.

[0043] Nanofiltration water flux and ion removal rate: Following GB / T34242-2017, at 25°C and an operating pressure of 0.50 MPa; the initial flux was recorded after the pure water flux stabilized for 30 minutes; the ion removal rate was determined using sodium sulfate and sodium chloride (2000 mg·L⁻¹ each). -1 According to the standard, the pure water flux / sodium sulfate removal rate / sodium chloride removal rate were calculated and recorded. The results are shown in Table 1.

[0044] Antifouling performance: Following the throughput test procedure of GB / T34242-2017, the contaminated solution was prepared with 1.0 g / L bovine serum albumin. -1 (25°C, 0.50MPa crossflow for 2h), the flux recovery rate (FRR) was measured after standard cleaning with deionized water for 10min. The results are shown in Table 1.

[0045] Acid and alkali resistance cycling: According to the acid and alkali resistance clause of GB / T34242-2017: hydrochloric acid solution pH 2 (25°C, 2h), deionized water rinsing, sodium hydroxide solution pH 11 (25°C, 2h), 5 cycles; record the sodium sulfate removal rate and pure water flux retention rate before and after the cycle, and the results are shown in Table 1.

[0046] Table 1 Performance Test Results project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Zeta potential (mV, pH7) −9.3 −6.8 −5.1 −10.7 −14.4 −12.6 −6.9 −7.5 −17.9 −7.9 Water contact angle (°) 44.9 41.7 39.6 47.2 43.8 49.5 42.1 45.6 54.3 43.2 Antibacterial rate of Escherichia coli (%) 99.2 99.6 99.4 97.9 36.4 93.8 99.2 98.5 96.8 99.0 Antibacterial rate against Staphylococcus aureus (%) 98.9 99.4 99.2 97.3 33.7 92.6 98.7 97.8 95.9 98.6 The antibacterial rate of Escherichia coli remained unchanged (50h, %). 95.1 98.7 97.9 92.4 30.5 80.2 90.3 84.8 72.6 88.6 Antibacterial rate against Staphylococcus aureus maintained (50h, %) 94.6 98.2 97.5 91.1 28.9 78.7 91.2 89.1 70.8 87.3 <![CDATA[Pure water flux (L·m -2 ·h -1 )]]> 66.3 63.4 54.2 64.8 61.7 66.1 64.2 58.7 78.4 62.9 Sodium sulfate removal rate (%) 97.6 98.4 99.1 97.5 98.2 96.8 98.1 98.1 92.3 97.9 Sodium chloride removal rate (%) 29.4 33.6 41.7 29.8 32.8 27.6 32.9 30.2 18.7 32.2 Post-contamination FRR (%) 92.1 94.6 92.3 88.9 93.9 86.7 93.1 92.0 80.4 92.6 Acid-base cycle flux maintained (%) 90.8 93.8 92.9 89.7 91.2 87.5 85.4 82.3 78.9 83.7 Acid-base cycle removal retention (%) 97.2 98.1 98.4 96.5 97.8 95.1 92.7 91.4 87.5 90.2 Data Analysis: As can be seen from the data in Examples 1-3 in Table 1, this invention synergistically introduces guanidinium-containing cations and zwitterions during interfacial polymerization, stabilizes monomer diffusion with a weak polyethyleneimine / tannic acid interfacial layer, and then utilizes maleimide with retained double bonds to trigger secondary addition after acid / base alternation, resulting in a synergistic distribution of strong cation-containing antibacterial sites and surface zwitterionic hydration in the separation layer along the thickness direction. This configuration makes the surface potential close to neutral, ensures sufficient surface hydration, significantly limits the initial adhesion of proteins and bacteria, and facilitates flux recovery after membrane fouling. At the same time, the dense cross-linking and anchoring effect reduces structural relaxation caused by long-term rinsing and acid-base cycling, thereby maintaining high divalent salt retention while also considering monovalent salt selectivity and durability.

[0047] As can be seen from the data in Table 1 for Example 2 and Comparative Example 1, omitting zwitterions in the initial aqueous phase leads to insufficient surface hydration, resulting in a simultaneous decrease in flux recovery and antibacterial retention after contamination. The main reason is the absence of zwitterions during the initial interfacial condensation stage, which reduces the density and continuity of hydrophilic groups near the surface, making it difficult to form a stable hydration layer. Although subsequent introduction can partially compensate for this, the embedding depth and covalent ratio are limited, weakening the synergistic effect.

[0048] As can be seen from the data in Example 2 and Comparative Example 2 in Table 1, the initial antibacterial activity decreased significantly when guanidinium-containing cations were absent, but the antifouling activity remained good. This is because zwitterions mainly provide hydration and anti-adhesion, while the contact bactericidal sites come from guanidinium-containing cations. When cation sites are absent, even if bacteria do not easily adhere, they are difficult to inactivate quickly, and residual viable bacteria increase after rinsing, making it difficult to achieve long-lasting antibacterial activity.

[0049] As can be seen from the data in Example 2 and Comparative Example 3 in Table 1, omitting the secondary aqueous phase leads to insufficient enrichment of amphoteric molecules on the surface, resulting in a simultaneous decrease in hydrophilicity and antifouling properties. The main reason is that in the "back and forth" time series, the secondary aqueous phase is used to enrich amphoteric molecules and embed them near the surface; the absence of this step leads to fragmentation of the amphoteric layer, insufficient regulation of interfacial energy and surface free energy, resulting in a phenomenon where, although the flux is high, the selectivity and antifouling properties are compromised and exacerbated.

[0050] As can be seen from the data in Table 1 for Example 2 and Comparative Example 4, when no maleimide crosslinking anchoring agent was added, the initial indicators were similar, but the durability decreased significantly. The main reason is that no subsequent Michael addition occurred, the free amines in the membrane and the terminal sites were not captured a second time, and the separation layer relaxed and micro-decomposed after long-term rinsing and acid-base cycling, resulting in a simultaneous decrease in antibacterial retention and cycling retention.

[0051] As can be seen from the data in Example 2 and Comparative Example 5 in Table 1, when the maleimide double bonds are completely deactivated, the initial removal rate does not increase significantly and the flux is actually lower. The main reason is the increase in volume fraction caused by the inert framework and the local pore blockage. Subsequent acid-base cycles also fail to achieve re-densification due to the lack of reactive double bonds, resulting in more significant degradation in durability.

[0052] As can be seen from the data in Example 2 and Comparative Example 6 in Table 1, when pretreatment is omitted, the throughput is abnormally high, but the selectivity and durability are significantly reduced. The main reason is the lack of fine control over interfacial tension and monomer diffusion by polyethyleneimine / tannic acid. Interfacial polymerization is more prone to forming defects and non-uniform micropores, exhibiting the characteristics of high throughput / low rejection / low FRR.

[0053] As can be seen from the data in Example 2 and Comparative Example 7 in Table 1, when only the acid segment is treated without the alkali segment to promote the reaction, the initial performance is acceptable, but the antibacterial and acid / alkali resistance are significantly insufficient. The main reason is that the alkali segment is beneficial for activating Michael addition and stabilizing the zwitterionic dissociation state; the lack of the alkali segment leads to insufficient anchoring reaction, and after long-term rinsing or pH cycling, the surface rearrangement and swelling are aggravated, and the synergistic effect is weakened.

[0054] from Figure 1 It can be seen that the sample is at 1653cm. -1 Strong amide I absorption was observed at 1542 cm⁻¹. -1The presence of amide II characteristics indicates that the release layer has a typical polyamide structure; 1775 / 1715cm -1 The imide carbon double peaks and 1670 cm⁻¹ -1 The guanidinium shoulder peaks together indicate the presence of maleimide anchoring structure and guanidinium group; 1203 and 1038 cm⁻¹ -1 The double strong peaks at S=O confirm the successful introduction of the amphoteric taurine group; 3390 cm⁻¹ -1 The broad peak is attributed to N–H / O–H hydrogen bond absorption.

[0055] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A method for preparing an antibacterial nanofiltration membrane, characterized by, The method comprises the following steps: (1) Interface layer pretreatment: immerse the polyether sulfone ultrafiltration membrane substrate in a pretreatment solution prepared from deionized water, branched polyethyleneimine and tannic acid for 10-30 min, take out and rinse to obtain a pretreated substrate; (2) First interfacial polymerization: immerse the pretreated substrate in an aqueous phase containing piperazine, guanidinium sulfate, taurine, sodium bicarbonate and polysorbate 20 for 5-15 min, roll to remove the residual liquid, then immerse in an isomeric alkane organic phase containing trimesoyl chloride for 5-15 min, roll to remove the residual liquid, to obtain a surface-treated substrate B; (3) Second water phase re-immersion: immerse the surface-treated substrate B in a water / isopropyl alcohol mixed solution containing taurine for 3-7 min, roll to remove the residual liquid, to obtain a surface-treated substrate C; (4) Preparation of a maleimide cross-linking anchor agent: react 4,4'-bismaleimide diphenylmethane with taurine and triethylamine in N,N-dimethylformamide, then add aminoguanidine bicarbonate for further reaction to obtain a cross-linking anchor agent retaining part of the maleimide double bond; (5) Anchoring and densification: add the cross-linking anchor agent to an isomeric alkane organic phase containing trimesoyl chloride, immerse the surface-treated substrate C for 15-25 min and roll to remove the residual liquid, to obtain a surface-treated substrate D; (6) Acid / alkali alternation and heat curing: immerse the surface-treated substrate D in a citric acid monohydrate solution and a sodium bicarbonate solution in sequence, then rinse and cure under hot air at 80-90°C for 5 min, to obtain an antibacterial nanofiltration membrane; The aqueous phase of step (2) is prepared by adding 3-5 g of piperazine, 0.5-1.5 g of guanidinium sulfate, 3-7 g of taurine, 0.5-1.5 g of sodium bicarbonate and 0.5-1.5 g of polysorbate 20 to 1000 mL of deionized water; the organic phase of step (2) is 1000 mL of Isopar G containing 0.5-1.5 g of trimesoyl chloride; the mixed solution of step (3) is a mixture of 950 mL of deionized water and 50 mL of isopropyl alcohol containing 7-13 g of taurine; the double bond retention amount of the cross-linking anchor agent retaining part of the maleimide double bond in step (4) is 20%-22%; in step (5), 0.03-0.07 g of the cross-linking anchor agent is pre-dissolved in 10 mL of ethyl acetate and then added to 1000 mL of Isopar G, and 0.8-1.2 g of trimesoyl chloride is added.

2. The method of claim 1, wherein the method is characterized by, The polyethyleneimine in step (1) is branched, and the weight average molecular weight is 24000-26000.

3. The method of claim 1, wherein the method is characterized by, The polyether sulfone ultrafiltration membrane substrate in step (1) has a size of 200 mm×200 mm, a molecular weight cut-off of 28-32 kDa, and a thickness of 115-125 μm.

4. The method of claim 1, wherein the method is characterized by, The pretreatment solution in step (1) is prepared by dissolving 1-3 g of branched polyethyleneimine and 0.5-1.5 g of tannic acid in 1000 mL of deionized water.

5. The method of claim 1, wherein the method is characterized by, The mass ratio of 4,4'-bismaleimide diphenylmethane, taurine, triethylamine and aminoguanidine bicarbonate in step (4) is 5:3:2:

1.

6. The method of claim 1, wherein the method is characterized by, The acid section in step (6) is dissolving 1-3 g of citric acid monohydrate in 2000 mL of deionized water and submerging for 1-3 min.

7. The method of claim 1, wherein the method is characterized by, The base section in step (6) is dissolving 1-3 g of sodium bicarbonate in 2000 mL of deionized water and submerging for 1-3 min.

8. An antibacterial nanofiltration membrane, characterized by, The preparation method of the antibacterial nanofiltration membrane according to any one of claims 1-7. The preparation method of the antibacterial nanofiltration membrane according to any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method of anti-pollution composite nanofiltration membrane

    CN110052179A

  • Dopamine and taurine modified polysulfone membrane and preparation method thereof

    CN112007526A

  • Polyamide composite reverse osmosis membrane with biological pollution resistance and preparation method thereof

    CN114053875A

  • High-flux nanofiltration membrane based on guanidyl compound as well as preparation method and application of high-flux nanofiltration membrane

    CN116510525A

  • Biological pollution resistant composite membrane as well as preparation method and application thereof

    CN118286895A